PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PEMBELIAN DI INDOMARET BATHIN ALAM OLEH MAHASISWA - Erika Kristia; Supira Supira; Dyanda Rahmadhani; Khusnul Fitri Astuti; Hutomo Atman Maulana (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
This study aims to analyze the influence of service quality and product quality on purchase satisfaction among students at Indomaret Bathin Alam. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM) method, the research involved 100 student respondents as samples. The validity and reliability tests indicate that the research instruments are valid and reliable. The R-Square value of 0.761 shows that service quality and product quality simultaneously explain 76.1% of the variation in purchase satisfaction. Hypothesis testing reveals that both variables have a positive and significant effect on purchase satisfaction, with product quality having a more dominant contribution. The research model also meets the model fit criteria with an SRMR value of 0.068. These findings emphasize the importance of managing product quality and improving service quality as key strategies to enhance customer satisfaction in the modern retail sector. The study recommends that Indomaret Bathin Alam’s management tighten product quality control and enhance staff training to boost customer loyalty. Furthermore, future research is suggested to broaden the respondent population and include other variables such as price and promotion for a more comprehensive understanding.